Identification of epigenetic mechanisms involved in seed coat development - Talarico, Emanuela; Angelone, Tommaso; Bruno, Leonardo (Università della Calabria, 2024)
The evolution of seeds is a fascinating aspect of evolutionary history and plant biology. Seeds have evolved over millions of years and are considered a significant adaptation that has contributed to the success of land plants. Seeds provide protection and a means of dispersal, enabling plants to reproduce successfully in a wide range of conditions. This evolutionary history has led to the rich diversity of plant species we see on Earth today. Seeds show remarkable adaptations to survive long journeys, including different shapes, sizes and mechanisms for dispersal. But none of these features would have been possible without the evolution of the ovule, within which sexual reproduction occurs. Indeed, ovule is the structure in which take place the formation of female gametophyte, fertilisation, embryogenesis and seed development upon fertilisation. In this scenario, the aim of this Ph. D. project was to identify, at evolutionary level, the molecular and epigenetic mechanisms involved in the ovule-to-seed switch in Ginkgo biloba plants. In particular, the focus was only on the pollination event, which in such a system is separated from fertilisation by a long time interval (i.e. four/five months). Indeed, Ginkgo biloba, a member of the gymnosperms and the only extant species of the order Ginkgoales, was used as experimental model because it is considered a living fossil due to its very ancient origins, dating back to the Permian period, the last period of the Palaeozoic, when an integument developed for the first time to cover the megasporangium. An interesting characteristic of Ginkgo, which makes it suitable for this purpose, is the production of fleshy fruit-like structures that are attractive to animals. Indeed, already after pollination, the integument takes on a consistency similar to that of mesocarp of fleshy fruit, leading to the hypothesis that it may represent a precursor to the fruit, although it cannot be identified as such because gymnosperms lack an ovary. Various approaches, including RNA sequencing, in situ gene expression, hormones localization and chromatin immunoprecipitation following by sequencing (ChIP-seq), on ovules at different stages were performed in order to identify the key pathways and the epigenetically regulated genes involved in ovule-seed switch. In order to identify the main pathways modulated by the crucial pollination event, three developmental stages of the Ginkgo ovule, collected immediately after the time frame in which pollination drop emission occurs, were used. In this context, pollination drop emission is an interesting aspect because, in many gymnosperms, it identifies the time point of possible pollen reception. Therefore, samples were collected from two different experimental fields, the first characterised by the presence of both male and female plants, and the second where only female plants are present. The two experimental fields are geographically distant from each other, which means that the plants in the second field are unable to receive pollen, so they are useful for understanding how ovule development proceeds in the absence of the pollination event. Moreover, this Ph. D. thesis was part of a larger project, which involved collaboration with the research groups coordinated by Professor Barbara Baldan, University of Padua, and Professor Lucia Colombo, University of Milan, helping to produce a large amount of data on Ginkgo, but also on Arabidopsis, which has always been the model species in plant biology. With the contribution also of the results we produced, it was possible to compare the two species and describe some of the key genes involved in ovule development in Ginkgo. Finally, most of the bioinformatic analyses related to the ChIP-seq experiment reported in this thesis were performed in collaboration with Professor Ernesto Picardi of the University of Bari Aldo Moro and Dr. Antonella Muto, post-doc in my research group at the University of Calabria.
UNIVERSITÀ DELLA CALABRIA Dipartimento di Biologia, Ecologia e Scienze della Terra Dottorato di Ricerca in Life Science and Technology CICLO XXXVI
Keywords: Epigenetica. Ormoni vegetali. Impollinazione.